2017
DOI: 10.1039/c7cp02692g
|View full text |Cite
|
Sign up to set email alerts
|

Investigation of the effects of phase transformations in micro and nano aluminum powders on kinetics of oxidation using thermogravimetric analysis

Abstract: Aluminum micro and nanoparticles are key ingredients in the synthesis of nano energetic materials. Hence it is important to characterize the kinetics and the rate controlling process of their oxidation. The literature shows that the mass diffusion and phase transformation within the aluminum oxide shell are important. However, the description of physical processes regarding simultaneous oxidation and phase transformation is lacking. In this paper, the controlled thermogravimetric (TGA) oxidation of 40-60 nm an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
15
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 26 publications
(15 citation statements)
references
References 33 publications
0
15
0
Order By: Relevance
“…Up to now, the controlling mechanism in low‐temperature oxidation is not understood in deep. It has been suggested that at the temperature below the melting point, a slow oxidation process is controlled by the diffusion of oxygen through the oxide shell . Based on the core–shell model as shown in Figure , herein, we use Fick's first law of diffusion to evaluate the diffusive flux of O 2 dNnormalO2dt=4πr2DTnormalcnormalO2r where r is the radius of ANPs, D(T) is the effective diffusion coefficient of O 2 in Al 2 O 3 or FAS‐17, and normalcnormalO2 is the molar concentration of O 2 .…”
Section: Discussionmentioning
confidence: 99%
“…Up to now, the controlling mechanism in low‐temperature oxidation is not understood in deep. It has been suggested that at the temperature below the melting point, a slow oxidation process is controlled by the diffusion of oxygen through the oxide shell . Based on the core–shell model as shown in Figure , herein, we use Fick's first law of diffusion to evaluate the diffusive flux of O 2 dNnormalO2dt=4πr2DTnormalcnormalO2r where r is the radius of ANPs, D(T) is the effective diffusion coefficient of O 2 in Al 2 O 3 or FAS‐17, and normalcnormalO2 is the molar concentration of O 2 .…”
Section: Discussionmentioning
confidence: 99%
“…where α is the reaction progress and m is a parameter that describes the nucleation and growth dimension based on ingestion and interface‐restricted nucleation and growth. This model was also used to describe the simultaneous phase transformations and oxidation of Al particles in an oxidizing atmosphere . The g ( α ) function for the power law model is given by g()α=α1/m, …”
Section: Resultsmentioning
confidence: 99%
“…The resulting kinetic parameters are apparent and dependent on the extent of the reaction (eg, species concentration or pressure, heat flow rates, etc). Meanwhile, it is possible to use Arrhenius equation with varying activation energy to describe the sequential thermally activated processes such as nucleation, growth, and diffusion in a heterogeneous reacting system …”
Section: Theoretical Approachesmentioning
confidence: 99%
See 2 more Smart Citations